Improvement of the crucial physiological characteristics of professional soccer players after competitional season - Olm, T.; Baskin, K.; Herde, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Despite massive research work there are different views on how long and how effectively aerobic endurance can be trained in elite soccer players. The aim of this study was to assess the changes of characteristics of the soccer players after a competition season. Methods: The subjects were 15 soccer players of the best club of Estonia. Average age was 22.5±2.8 years. The test battery included electro-, echo- and polycardiography, and incremental treadmill test to exhaustion. Anticipation speed and correctness were assessed. Correlation coefficients were calculated.All indices were compared with the identical indices received one year ago from the same players at the same pre-seasonal period. Results: From 29 compared means six hadn`t changed: height (181.5±6.4 cm), body mass (74.7±3.2 kg), body fat (11.3±2.1%), blood pressure (123/72 mmHg), anticipation speed (0.574±0.07 sec) and anaerobic threshold (181.1±6.0 beat/min at L 4 mmol/l). Statistically significant improvements were found in four characteristics: VO2max (62.8±3.8 ml/kg/min), VO2 (4.6±0.3 l/min), maximal ventilation (174.6±19.3 l/min) and maxBLa (12.4±2.7 mmol/l). The remainings indices showed a tendency to improve, but not that strongly. Discussion: From results we can see that the most changeable characteristics are those which are related to the energy systems. VO2max increased by 8.5%. A similar increase (by 8.6%) was reported by J. Helgerud et al. (2011). The improvement of O2 uptake was accompanied by an increase of maximal ventilation by 6,6%. Heart stroke volume, heart mass/volume index increased without a significant difference of the means. The anaerobic threshold was surprisingly stable: 181,1±6,0 versus 181,6±6,8 beat/min a year ago. Similar results were reported by K. McMillan et al. (2012). B. Sterzing et al. (2011), assessing levels of aerobic endurance in young soccer players, found that neither anaerobic thresholds nor velocity at 4 mmol/l lactate differed significantly between the age groups U16, U17 and U19. Only the U23 group showed significant difference to younger age groups. The authors` opinion is that the higher aerobic capacity in U23 players is based on a selection of players. Conclusion: The results of the study support previous researches indicating that adult professional players, having relatively high-level physiological characteristic, can improve them. We are convinced that as the anaerobic threshold is not a very changeable, involving other characteristics in assessment of aerobic capacity is necessary.